2007
DOI: 10.1086/514342
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Vaccine to Prevent Herpes Zoster and Postherpetic Neuralgia in Older Adults

Abstract: The cost-effectiveness of the varicella zoster vaccine varies substantially with patient age and often exceeds $100,000 per quality-adjusted life year saved. Age should be considered in vaccine recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
112
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 46 publications
0
112
1
2
Order By: Relevance
“…32,33 Finally 14 cost-effectiveness studies of HZ vaccination remained and were systematically reviewed. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Main study characteristics Table 1 summarizes the main characteristics of the included studies ordered by publication date. Several studies did not mention all the main features reported in Table 1, such as time horizon, costing year, sensitivity analysis and funding.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…32,33 Finally 14 cost-effectiveness studies of HZ vaccination remained and were systematically reviewed. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Main study characteristics Table 1 summarizes the main characteristics of the included studies ordered by publication date. Several studies did not mention all the main features reported in Table 1, such as time horizon, costing year, sensitivity analysis and funding.…”
Section: Study Selectionmentioning
confidence: 99%
“…Country and funding Of the 14 studies included, 9 were conducted in European countries (UK, Belgium, The Netherlands, Switzerland and France) [34][35][36][37][38][39][40][41][42][43][44][45][46][47] and 5 in non-European countries (US and Canada). [35][36][37][38][39] Six studies were funded by the pharmaceutical industry, 36,38,41,42,44,46 five studies by public resources 34,37,39,40,43,45 and two studies were performed without external funding.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations